2005
DOI: 10.1111/j.1440-1746.2005.03894.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cytokeratin 20 mRNA in the peripheral blood of patients with colorectal cancer by immunomagnetic bead enrichment and real‐time reverse transcriptase–polymeras chain reaction

Abstract: The combined use of negative and positive immunomagnetic beads followed by amplification of CK20 mRNA by means of RT-PCR is a non-invasive, sensitive, and specific assay for the detection of circulating colonic cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…This step will allow the direct visualisation and quantification of isolated tumour cells. Alternatively, PCR-based analyses may allow the evaluation of expression of cancerspecifi c genes from blood samples [12,13]. Molecular-based approaches have been very popular for the detection of CTCs [14,15].…”
Section: Methods For the Detection And Isolation Of Ctcsmentioning
confidence: 99%
“…This step will allow the direct visualisation and quantification of isolated tumour cells. Alternatively, PCR-based analyses may allow the evaluation of expression of cancerspecifi c genes from blood samples [12,13]. Molecular-based approaches have been very popular for the detection of CTCs [14,15].…”
Section: Methods For the Detection And Isolation Of Ctcsmentioning
confidence: 99%
“…In gastric cancer, the detection rate of CTC in blood ranged from 0% to 53.3%, and the correlation between CTC and recurrence or prognosis was found in 4 of 7 studies [15][16][17][18][19][20][21]. In colorectal cancer, the detection rate of CTC in blood ranged from 15.0% to 72.5%, and a relationship between CTC and recurrence or prognosis was found in 8 of 13 studies [22][23][24][25][26][27][28][29][30][31][32][33][34]. The reason for the different results was perhaps the various primers used for the RT-PCR method.…”
Section: Conclusion and Perspectivementioning
confidence: 97%
“…This study has been corroborated by a number of other studies. 82,100 A recent study performed by Guo and coworkers 101 detected CK20 mRNA intracellularly in 72.5 to 82.5 percent in CTC of 40 patients with CRC by using a combination of positive and negative immunomagnetic isolation and real-time PCR. They demonstrated that CK20 mRNA presence in CTC correlates significantly with the tumor size and lymphatic and hepatic invasion but not the grade of differentiation.…”
Section: Human Telomerase Reverse Transcriptase Mrnamentioning
confidence: 98%